BAHASA AGAMA DALAM IKLAN AL QODIRI DAN SANTRI - Khairuddin . (Indonesian Journal of Islamic Communication, 2020)
Consuming drinking water in the Bottle seems unstoppable along with the changing times, the influence of consumptive culture and the lifestyle of modern society. The Changes of public consumption based on fulfilling desires, strengthening cultural and religious identities and instead of following trends are the impact of globalization and modernization. However, it has begun to penetrate into the realm of consumption of daily necessities, such as choicing of drinking water, food, fashion labeled halal, or more generally products labeled with religion. This study aims to determine the signs, markers and markers or the meaning of myths contained in Al Qodiri and SANTRI Bottled Mineral Water advertisements. This study used constructivism paradigm with the type of qualitative research and used Roland Barthes' semiotic analysis to answer the problem formulation. The results of semiotic analysis on advertisements show that there are denotative meanings and connotative meanings as well as the meaning of myths in advertising products. As for the denotation of the AMDK Al Qodiri advertisement, the name on the brand is the name of the Islamic boarding school, the two words Al Qodiri come from Arabic which means that they refer to the nature of Allah, the Almighty. The connotative meaning of Al Qodiri shows that the water that is produced is healthy and contains baraka, which connotatively the language of "healthy" is scientific legitimacy and "barokah" is theological legitimacy. The mode of commodification of religion in the two advertising products shows that the implied meaning through advertising is that there is an economic value orientation to be achieved, although implicitly in the profiles of the two companies, they also have positive goals for the development of Islamic boarding schools